2015
DOI: 10.1111/jnc.13406
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Pax6 contributes to the induction of GLT‐1 expression in astrocytes through an interaction with a distal enhancer element

Abstract: The Na+-dependent glutamate transporter, GLT-1 (EAAT2), shows selective expression in astrocytes, and neurons induce expression of GLT-1 in astrocytes. In unpublished analyses of GLT-1 promoter reporter mice, we identified an evolutionarily conserved domain of 467 nucleotides ~8 kb upstream of the GLT-1 translation start site that is required for astrocytic expression. Using in silico approaches, we identified Pax6 as a transcription factor that could contribute to the control of GLT-1 expression by binding wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…As such, glutamate transporters make for good potential therapeutic targets. However, our understanding of the complex regulation of glutamate transporter transcription and translation (Ghosh et al, 2011(Ghosh et al, , 2015(Ghosh et al, , 2016, cell surface expression and stabilisation (Stenovec et al, 2008;Yang et al, 2009Yang et al, , 2010Underhill et al, 2015), and internalisation Sheldon et al, 2008;Underhill et al, 2014;Ib añez et al, 2016) is still rather limited. Deciphering the mechanisms by which glutamate transporters are expressed and stabilised at the cell surface is of utmost importance, as it could reveal innovative targets for the treatment of diseases such as traumatic brain injury or epilepsy where extracellular glutamate is high.…”
Section: Glutamate Transporters As Potential Therapeutic Targetsmentioning
confidence: 99%
“…As such, glutamate transporters make for good potential therapeutic targets. However, our understanding of the complex regulation of glutamate transporter transcription and translation (Ghosh et al, 2011(Ghosh et al, , 2015(Ghosh et al, , 2016, cell surface expression and stabilisation (Stenovec et al, 2008;Yang et al, 2009Yang et al, , 2010Underhill et al, 2015), and internalisation Sheldon et al, 2008;Underhill et al, 2014;Ib añez et al, 2016) is still rather limited. Deciphering the mechanisms by which glutamate transporters are expressed and stabilised at the cell surface is of utmost importance, as it could reveal innovative targets for the treatment of diseases such as traumatic brain injury or epilepsy where extracellular glutamate is high.…”
Section: Glutamate Transporters As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Two groups essentially simultaneously realized that rat astrocytes in culture express little or no GLT-1 protein, but co-culturing astrocytes with neurons induces expression of GLT-1 in astrocytes (Schlag et al, 1998, Swanson et al, 1997). In fact, several subsequent studies have documented low levels of GLT-1 in mouse astrocyte cultures, but neurons also increase GLT-1 transcription in this system (Apricó, Beart, Crawford & O’Shea, 2004, Ghosh, Lane, Krizman, Sattler, Rothstein & Robinson, 2015, O’Shea, Lau, Farso, Diwakarla, Zagami, Svendsen et al, 2006). The effect of neurons is at least in part dependent upon soluble factors but it may also depend on contact (Drejer, Meier & Schousboe, 1983, Gegelashvili et al, 1997, Gegelashvili et al, 2000, Yang, Gozen, Watkins, Lorenzini, Lepore, Gao et al, 2009, Zelenaia et al, 2000).…”
Section: Why Study Transcriptional Regulation Of Glutamate Transpomentioning
confidence: 94%
“…While the proximal 2.5kb promoter of GLT-1 gene is highly conserved and has been well characterized, there are several additional evolutionary conserved domains distal to this region out to ~12.5kb from the translation start site (Figure 1) (Ghosh et al, 2015). Analyses of promoter reporter mice generated by Rothstein and his colleagues have revealed that the proximal 7.9 kb of the promoter is not sufficient to direct astrocytic expression of reporter protein, reporter is observed mostly in neurons (Rothstein unpublished observations; for discussion, see Ghosh et al, 2015).…”
Section: Why Study Transcriptional Regulation Of Glutamate Transpomentioning
confidence: 99%
See 2 more Smart Citations